2014
DOI: 10.1111/1756-185x.12331
|View full text |Cite
|
Sign up to set email alerts
|

Association of perceived neighborhood characteristics, socioeconomic status and rural residency with health outcomes in Egyptian patients with systemic lupus erythematosus: one center study

Abstract: Study findings indicate that poor socioeconomic status, rural residency and perceived neighborhood characteristics are associated with depression; worse perceived neighborhood aesthetics and safety are associated with lower SF-36 physical functioning, and worse neighborhood social cohesion is associated with higher disease activity among patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…A single center cross-sectional study on 80 Egyptian patients with aSLE supported the finding that poor socioeconomic status and rural residency are associated with lower SF-36 physical functioning and higher disease activity. 39 Other studies from Egypt, that have been done on patients from the free-of-charge tertiary university hospitals showed similar results to our cohort. Renal manifestations were found in 67% and 72.2% of patients with cSLE in two previous studies from Cairo University hospitals respectively 40 , 41 and 72.5% in a smaller study from other tertiary university hospitals in Cairo (Ain Shams University Hospitals).…”
Section: Discussionsupporting
confidence: 90%
“…A single center cross-sectional study on 80 Egyptian patients with aSLE supported the finding that poor socioeconomic status and rural residency are associated with lower SF-36 physical functioning and higher disease activity. 39 Other studies from Egypt, that have been done on patients from the free-of-charge tertiary university hospitals showed similar results to our cohort. Renal manifestations were found in 67% and 72.2% of patients with cSLE in two previous studies from Cairo University hospitals respectively 40 , 41 and 72.5% in a smaller study from other tertiary university hospitals in Cairo (Ain Shams University Hospitals).…”
Section: Discussionsupporting
confidence: 90%
“…This association was present even though the patients with low education were on average older at the onset of their SLE (so education would have been completed years before SLE onset for the vast majority). Previous studies demonstrated a link between low SES and worse SLE patient outcomes in disease activity, disease damage, mortality, and quality of life . However, most studies were from health care systems that did not have universal coverage that could marginalize those with low education .…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that childhood SES influences adult health, independent of SES as an adult . In previous studies of SES influencing SLE, disease activity was measured using different assessment tools: SLEDAI , SLAM , and Systemic Lupus Activity Questionnaire . We used both SLEDAI‐2K and SLAM, but only SLEDAI‐2K was affected by low education.…”
Section: Discussionmentioning
confidence: 99%
“…Low SES is associated with depression . Specifically, access to less effective treatment and medications within low SES and less developed countries is related to worse outcomes overall.…”
Section: Discussionmentioning
confidence: 99%